Graphics Card Computing for Cosmology: Cholesky Factorization - Gratton, Steven (2010 IEEE 10th International Conference on Computer and Information Technology, 2010)
Cosmological data sets are becoming so large as to make optimal statistical analyses of them impossible. Even with approximations made, the computational challenges can be severe. Cholesky Factorization of matrices is an essential tool. This paper reports on progress made by the author in implementing Cholesky Factorization on one or more graphics processing units (GPUs). Particular attention is paid to the process of the development of the algorithm in light of the characteristic features of the GPUs. Performance and optimization are discussed, and potential avenues for future development are presented.